Evaluation of soybean meal from different sources as an ingredient in practical diets for Pacific white shrimp Litopenaeus vannamei. (12th February 2019) - Galkanda Arachchige, Harsha Sameera Chathuranga; Qiu, Xuan; Stein, Hans H.; Davis, Allen
Abstract: Solvent extracted soybean meal (SBM) is generated using different varieties of soybeans grown under a range of conditions and then processed at different crushing plants. Due to its competitive cost and availability, it is a popular plant‐based protein source for shrimp feed formulations. However, there is limited information about effects of variations in the nutritional composition of soybean meal have on performances of shrimp. Hence, the present study was designed to determine the effects of different soybean sources on the growth performances of Litopenaeus vannamei . Two growth trials were conducted with iso‐nitrogenous and iso‐lipidic (350 g/kg protein and 80 g/kg lipid) test diets formulated with 25 sources of soybean meal. Trial one incorporated 14 treatments including a soy‐based diet containing 517 g/kg SBM (eight replicates) and this soy source was then replaced with 13 different soybean sources (four replicates per treatment). The second trial used the same basal diet and 11 different sources of soybean meal (Total 12 diets) with five replicates per treatment. Both growth trials were conducted with a stocking density of 10 shrimps/aquarium in a semi‐closed recirculating system and the initial weight of shrimps for trials 1 and 2 were 0.23 g ± 0.02 and 0.67 g ± 0.02 respectively. During the two trials, shrimp were fed four times/day assuming a FCR of 1.8, over 42 days for trial 1 and 35 days for trial 2. Results indicated that there are differences among sources of soybean meal for standardized percentage TGC. Diet 21 that contained SBM4550 had the largest value for TGC whereas the lowest value for TGC was observed for shrimp fed diet 17 that contained SBM45536. According to the statistical analysis that was used to interpret the growth performance data from the complete chemical profile of the SBM, phosphorous, phytate‐phosphorous and total phytic acid levels had positive correlations ( p < 0.005) with TGC whereas raffinose ( p = 0.086) had a negative correlation with TGC. Results of this work indicates phosphorous, phosphorous in phytic acid and total phytic acid and raffinose are important components in SBM that may have significant effects on the growth performances of pacific white shrimp.